2020
DOI: 10.7759/cureus.8513
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylurea-Induced Hypoglycemia in a Patient With Cirrhosis

Abstract: Type 2 diabetes mellitus is highly prevalent among patients with cirrhosis. The pharmacological management of this disease in patients with chronic liver disease remains controversial, however. Insulin secretagogues such as sulfonylureas are associated with a high risk of hypoglycemia among diabetics. In patients with cirrhosis, this risk is more pronounced due to decreased hepatic clearance, concurrent alcoholism, hypoalbuminemia, and acute liver decompensation. In this case report, we present a case of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…American Diabetes Association (ADA) has declared acarbose safe and well-tolerated in patients with CLD, but it increases the risk of hyperammonemia in patients with advanced hepatic impairment [9]. Sulphonylureas, another oral hypoglycemic agent must be avoided in people with cirrhosis due to reduced hepatic clearance, and risk of hypoglycemia, hypoalbuminemia and acute liver decompensation [38]. A longitudinal cohort of Taiwan's National Health Insurance Research Database (>1 million patients with compensated cirrhosis) reported higher risk of mortality and decompensation with metformin [39], decompensated cirrhosis, variceal bleeding and hepatic failure with dipeptidyl peptidase-4 inhibitor [40] and higher risk of all-cause mortality with insulin use [41].…”
Section: Pharmacological Management Of Hepatogenous Diabetes: a Chall...mentioning
confidence: 99%
“…American Diabetes Association (ADA) has declared acarbose safe and well-tolerated in patients with CLD, but it increases the risk of hyperammonemia in patients with advanced hepatic impairment [9]. Sulphonylureas, another oral hypoglycemic agent must be avoided in people with cirrhosis due to reduced hepatic clearance, and risk of hypoglycemia, hypoalbuminemia and acute liver decompensation [38]. A longitudinal cohort of Taiwan's National Health Insurance Research Database (>1 million patients with compensated cirrhosis) reported higher risk of mortality and decompensation with metformin [39], decompensated cirrhosis, variceal bleeding and hepatic failure with dipeptidyl peptidase-4 inhibitor [40] and higher risk of all-cause mortality with insulin use [41].…”
Section: Pharmacological Management Of Hepatogenous Diabetes: a Chall...mentioning
confidence: 99%